2002
DOI: 10.2307/3079114
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Spatial Patterns in Malaysian Tree Species

Abstract: Tree species in tropical rain forests exhibit a rich panoply of spatial patterns that beg ecological explanation. The analysis of tropical census data typically relies on spatial statistics, which quantify the average aggregation tendency of a species. In this article we develop a cluster-based approach that complements traditional spatial statistics in the exploration and analysis of ecological hypotheses for spatial pattern. We apply this technique to six study species within a fully mapped 50-ha forest cens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Continuum percolation (Meester and Roy, 1996) was first applied to spatial analysis of individual mapped tree locations by Plotkin et al (2002), who introduced a method to detect spatial clusters (clumps) in tree maps, and used the approach to investigate habitat associations of Malaysian tree species. Recently, forest scientists working to characterize reference spatial patterns to inform forest restoration have independently converged on this approach (Larson and Churchill, 2008;Abella and Denton, 2009;Sánchez Meador et al, 2011).…”
Section: Continuum Percolation To Detect Clumps and Single Treesmentioning
confidence: 99%
“…Continuum percolation (Meester and Roy, 1996) was first applied to spatial analysis of individual mapped tree locations by Plotkin et al (2002), who introduced a method to detect spatial clusters (clumps) in tree maps, and used the approach to investigate habitat associations of Malaysian tree species. Recently, forest scientists working to characterize reference spatial patterns to inform forest restoration have independently converged on this approach (Larson and Churchill, 2008;Abella and Denton, 2009;Sánchez Meador et al, 2011).…”
Section: Continuum Percolation To Detect Clumps and Single Treesmentioning
confidence: 99%
“…The table does not include studies in which the term was used only as a general term without explanation (35 studies). Even though not mentioned by the authors, we consider the terms safesite limitation (van der Meijden et al 1992), and nichebased limitation (Plotkin et al 2002) synonyms to microsite limitation and include these studies in our comparison. The results of this review clearly show that there is no consistency in the usage of the terms (Table 1), thus, supporting the need of consistent definitions.…”
Section: The Termsmentioning
confidence: 99%
“…Clark et al 1998Clark et al , 1999John et al 2007), but other studies have shown that dispersal limitations could yield similar aggregated distributions if a species were not able to disperse to all suitable sites and instead established near the parent trees (Hubbell 1997;Dalling et al 2002). Some researchers argue that species distributions in plant communities are determined by both processes (Coomes et al 1999;Plotkin et al 2002;Lancaster 2006;Wiegand et al 2007). Analyzing species-environment associations is one effective way to assess the influence of habitat association on species distributions.…”
Section: Introductionmentioning
confidence: 99%
“…However, as described above, the fact that dispersal limitation may also lead to species aggregation challenges researchers to understand the underlying process of species distributions. Many statistical methods were proposed to resolve this problem Plotkin et al 2002;Diggle 2003). In particular, spatial point process models are a particularly promising method recently developed to address this issue (Moller and Waagepetersen 2003;Waagepetersen 2007).…”
Section: Introductionmentioning
confidence: 99%